Application of a Chilled Ammonia-based Process for CO2 Capture to Cement Plants. (July 2017) - Pérez-Calvo, José-Francisco; Sutter, Daniel; Gazzani, Matteo; Mazzotti, Marco
Abstract: The chilled ammonia process (CAP) is considered one of the most promising alternatives to amine-based absorption processes for post-combustion carbon capture applied to power plants. This work provides an insight on the CAP adaptations required to meet the conditions found in the flue gas emitted in cement plants, where CO2 generation is inherent to the manufacturing process. A rate-based model has been validated to simulate the CO2 absorber of the CAP for cement plant-like flue gas composition in order to obtain the Murphree efficiencies to be used in full CAP simulations in Aspen Plus. A preliminary minimum exergy need of 0.92 MJ/kgCO2 has been found for the CAP applied to the cement plant case making use of an optimization algorithm and capturing 85.2% of the emitted CO2 . Higher temperatures (> 45 °C) are found in the CO2 absorber of the CAP when applied to cement plant-like flue gas conditions in comparison to the power plant case (< 40 °C), requiring a lower pumparound temperature in order to control the ammonia slip in the CO2 -depleted flue gas exiting the column.